Assessment Report of the Café de Paris Initiative and its Impact in New Brunswick. - Consortia and Associate.s (Société Santé et Mieux-être en français du Nouveau-Brunswick, 2021)
pages: 36

L'effectivité des lois linguistiques dans le secteur de la santé - Forgues, Éric; Maillet, Stéphanie (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Cet article découle d’une étude qui problématise le concept d’effectivité des lois linguistiques. Dans cette étude, nous cherchions à mieux comprendre les dimensions juridiques, sociales, organisationnelles et psychologiques qui peuvent agir sur l’effectivité des lois linguistiques dans le secteur de la santé dans les provinces du Canada qui disposent de telles lois. Sachant que les professionnels de la santé sont en première ligne pour offrir des services en français, nous avons analysé leurs perceptions en ce qui concerne divers aspects pouvant influencer l’offre de services en français. Les résultats montrent que des différences souvent significatives s’observent entre les répondantes et les répondants anglophones et francophones et ceux qui oeuvrent dans des hôpitaux anglophones et francophones. Les résultats révèlent également que des efforts doivent se poursuivre pour atteindre une effectivité accrue, tout en offrant des pistes pour mieux orienter ces efforts. Mots-clés : effectivité des lois linguistiques, santé en français, francophonie, langue de service, minorités linguistiques

L'effectivité des lois linguistiques dans le secteur de la santé. Rapport - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

L'effectivité des lois linguistiques dans le secteur de la santé. Sommaire - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

Language barriers and healthcare access: a qualitative study in the Volta Region of Ghana - Glover-Meni, Nathaniel; Nyarko, Joy Ato; Agbezorlie, Peter K.; Agyei, Dominic Dankwah (Journal of Communication in Healthcare, 2024)
Background The study explores the language barriers between two language minority populations and healthcare professionals in the Volta Region of Ghana. Methods An interpretive description with a qualitative approach to data collection and analysis was used. This study was carried out in the Tafi-Atome and Avatime-Vane communities, the Hohoe Municipal Hospital and the Margaret Marquart Catholic Hospital in the Kpando Municipality. In all, 46 respondents comprising 19 purposively sampled community members (patients) from the two selected communities and 27 conveniently sampled healthcare professionals from the two health facilities were interviewed. The face-to-face in-depth interviews were audio-recorded, transcribed and thematically analysed. Results The study revealed a barrier in language use between healthcare professionals and patients from the two language minority communities. While healthcare professionals preferred to use English, Akan and Ewe, the patients, on the other hand, preferred their native languages, which are Sideme and Tegbor. The services of unqualified interpreters were utilised by both healthcare professionals and patients. Study participants were aware of these challenges, which prevented the patients from receiving optimum healthcare services, and the healthcare workers from delivering client-centred healthcare services. Conclusions The presence of communication challenges emanating from language barriers between healthcare professionals and patients should be considered as a key hindrance to the attainment of the Sustainable Development Goal Three (SDG3), which aims to promote health and well-being at all ages. Therefore, stakeholders in the healthcare delivery system in Ghana need to prioritize stronger communication and translation practices and policies.

Official Language Minority Communities in Ontario: Understanding the Lived Experiences of Francophone Patients and their Nursing Care Providers - Muray, Mwali (Université d'Ottawa/University of Ottawa, 2022)
Although Canada is a bilingual country, official language minority community patients struggle to access quality care in their language. This reality has been of concern for Francophone minority communities in Ontario, but has seldom been examined in a nursing context. This research sought to examine the lived experiences of registered nurses and nursing students providing care to French-speaking patients in Ontario, as well as the realities of Francophone patients seeking French language health care services in Ontario. The conceptual frameworks guiding the study were the “Four Levels of Change for Improving Quality” model and the “Four-Level Model of the Health Care System.” Using qualitative phenomenological inquiry, as influenced by Martin Heidegger and Max van Manen, 31 semi-structured interviews were conducted with three subsets (n=10 Francophone patients; n=10 nursing students; n=11 registered nurses) throughout Ontario who had experience with the phenomenon being investigated. Data collection took place over a year (2018-2019) and was analysed thematically. Significant findings were identified across the three groups. Participants revealed the patchwork of individual actions taking place to remedy the existing gaps regarding care for Francophone minority populations. This included navigating a health care system where good enough care was the unfortunate standard for Francophone patients, and discussing how Francophone patients and nursing care providers implement strategies individually to manage the lack of resources for Francophone patient populations in Ontario. This thesis asserts that official language minority communities and their nursing care providers remain faced with difficulties providing and receiving care in Ontario. While numerous structures and resources exist to remediate the problems, these interventions and resources are not always implemented systemically, leading to a disproportionate burden on individuals, significant risks for safety for patient populations, and ethical dilemmas for nursing care providers. Recommendations are provided to bridge the gaps and ensure considerations of the needs of linguistic minorities throughout the health care system. Keywords: Francophonie, Linguistic Minorities, Nursing, Phenomenology, Qualitative Research

Official Language Minority Communities in Ontario: (In)visibility of Nursing Care - Muray, Mwali; Chartrand, Julie; Perron, Amélie (Aporia, 2026)
Despite Canada’s linguistic duality, French-speaking minority populations continue to face significant barriers in accessing equitable health care. Investigating two key research questions, this study explores: (1) What are the lived experiences of registered nurses and nursing students caring for French-speaking patients in Ontario? and (2) How do French-speaking patients navigate the health care system to access care in their preferred language? Using qualitative methodology informed by interpretive phenomenology, 31 participants were interviewed individually between 2018 and 2019, offering firsthand accounts of their experiences. Findings reveal a paradox of (in)visibility: French-speaking patients and nursing providers remain invisible when they adapt to systemic shortcomings but become highly visible when they advocate for equitable care. The study highlights the urgent need for the effective and consistent implementation of the strategic changes within health care institutions. Addressing these linguistic disparities is not only a matter of patient safety and quality care but also a fundamental step toward upholding Canada’s bilingual commitments in health service delivery.